Synthesis and thermal study of magnesium complexes with 8-hydroxyquinolinate derivatives - Guerreiro, CTR; Ribeiro, Clovis Augusto [UNESP]; Crespi, Marisa Spirandeli [UNESP]; Torres, C. (Kluwer Academic Publ, 2002)
Magnesium ion was reacted with 5,7-dibromo-, 5,7-dichloro-, 7-iodo- and 5-chloro-7-iodo-8-hydroxyquinoline, in acetone/ammonium hydroxide medium under constant stirring to obtain (I) Mg[(C9H4ONBr2)(2)].2H(2)O; (II) Mg[(C9H4ONCl2)(2)].3H(2)O; (III) Mg[(C9H5ONI)(2)].2H(2)O and (IV) Mg[(C9H4ONICl)(2)].2.5H(2)O complexes. The compounds were characterized by elemental analysis, IR spectra, ICP, TG-DTA and DSC.Through thermal decomposition residues were obtained and characterized, by X-ray diffractometry, as a mixture of hexagonal MgBr2 and cubic MgO to the (I) compound at 850degreesC; cubic MgO to the (II), (III) and (IV) compounds at 750, 800 and 700degreesC, respectively.
Keywords: 8-hydroxyquinolinate derivatives; magnesium; thermal decomposition